Organizational altercasting: Developing impression management and cyber‐risk disclosures - Łada, Monika; Kozarkiewicz, Alina; Haslam, Jim; Kabalska, Agnieszka; Mueller, Frank (Contemporary Accounting Research, 2025)
The study develops theorizing of external organizational communications that entail impression management. This includes developing linkages to Goffman's work and a Goffmanian research tradition. Our approach innovatively articulates dimensions of impression management entailing the presentation of others and nuanced practices of what we term organizational altercasting (OAC). Altercasting has been conceptualized in a Goffmanian tradition. OAC, seen as implicated in more developed organizational impression management (OIM), involves an organization constructing for another/others (an audience with whom the organization interacts) a persona that is congruent with the organization's goals. Our theorizing also innovatively draws from Goffmanian insight in a coherently associated way—namely, by appreciating the pervasiveness of interaction rituals, including those that take place in an organizational communication style using today's technology. We suggest that OAC especially tends to entail tact. The empirical focus is a case analysis of a Polish bank (CB) facing challenges of cybersecurity and disclosing/communicating externally on cybersecurity/cyber‐risk. For insight, we address this question: In terms of a developed theorizing of OIM (including OAC), how did the bank respond to external challenges, related to cybersecurity, through public disclosures/communications? A content analysis of types of multimedia, with attention given to context, indicated the importance of the presentation of others. We were drawn to how CB's customers, a key audience, were presented in CB's external communications, highlighting long‐term engagement in, and an increase in the significance of, these communications. For our case, articulation of OIM and the presentation of others was further developed through OAC, with particular attention given to communication style vis‐à‐vis modern technology. Our work promotes OAC's wider applicability, including beyond cyber‐risk disclosures.